2014
DOI: 10.1002/aenm.201301655
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Supercapacitors Based on Bacterial Cellulose Paper Electrodes

Abstract: Supercapacitors based on freestanding and flexible electrodes that can be fabricated with bacterial cellulose (BC), multiwalled carbon nanotubes (MWCNTs), and polyaniline (PANI) are reported. Due to the porous structure and electrolyte absorption properties of the BC paper, the flexible BC‐MWCNTs‐PANI hybrid electrode exhibits appreciable specific capacitance (656 F g−1 at a discharge current density of 1 A g−1) and remarkable cycling stability with capacitance degradation less than 0.5% after 1000 charge–disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
121
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(124 citation statements)
references
References 46 publications
2
121
0
1
Order By: Relevance
“…Nanostructured CPs are expected to show desirable energy storage performance due to their high surface area and short path lengths for ion migration as well as good electrochemical activity. Thus, substantial effort has been dedicated to deposit nanoscaled CPs on substrates with high surface area to achieve the preferred capacitance (Nyström et al 2009(Nyström et al , 2012Kim et al 2012;Sultana et al 2012;Yue et al 2012;Liang et al 2013;Li et al 2014;Wu et al 2014). Nyström et al reported a nanostructured high surface area electrode material composed of cellulose fibers from Cladophora algae individually coated with a 50 nm thin layer of PPy, giving rise to a new flexible device with a charge capacity of 33 mAh g -1 and a capacity retention of over 94 % after 100 cycles (Nyström et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Nanostructured CPs are expected to show desirable energy storage performance due to their high surface area and short path lengths for ion migration as well as good electrochemical activity. Thus, substantial effort has been dedicated to deposit nanoscaled CPs on substrates with high surface area to achieve the preferred capacitance (Nyström et al 2009(Nyström et al , 2012Kim et al 2012;Sultana et al 2012;Yue et al 2012;Liang et al 2013;Li et al 2014;Wu et al 2014). Nyström et al reported a nanostructured high surface area electrode material composed of cellulose fibers from Cladophora algae individually coated with a 50 nm thin layer of PPy, giving rise to a new flexible device with a charge capacity of 33 mAh g -1 and a capacity retention of over 94 % after 100 cycles (Nyström et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…[97] Moreover, the network is made up of a random assembly of cellulose nanofibers with a high aspect ratio and a diameter of 20-100 nm. [16,98] As a result, BC exhibits a large specific surface area. Furthermore, it can be industrially manufactured via the microbial fermentation process at a very low price.…”
Section: Thermal Transformation Approachmentioning
confidence: 99%
“…Furthermore, the incorporation of PANI into porous flexible BC/MWNT paper through a simple anodic polymerization had a negligible influence on its mechanical strength and flexibility, as shown in Figure 10a. [160] The effect of different polymerization times for the PANI on the C sp of BC/MWNT/PANI (Figure 10b) was studied, and the C sp values were estimated to be 367, 442, 656, 557, and 375 F g −1 at a discharge current density of 1 A g −1 for the BC/ MWNT/PANI x electrodes with various polymerization times (x = 2, 5, 10, 15, and 20 min, respectively). The C sp value of the BC/MWCNTs/PANI 10 (656 F g −1 , 1 A g −1 ) is much larger than functionalized GN-PANI composite (388 F g −1 , 1 A g −1 ), [161] and comparable to the paper-Au/PANI composite electrode (560 F g −1 , 2.13 A g −1 ) [162] and GN-PANI paper (763 F g…”
Section: Bio-macromolecule and Conducting Polymer Based Compositesmentioning
confidence: 99%